2006
DOI: 10.1002/anie.200602952
|View full text |Cite
|
Sign up to set email alerts
|

Lead Chalcogenide Nanotubes Synthesized by Biomolecule‐Assisted Self‐Assembly of Nanocrystals at Room Temperature

Abstract: Natural help: PbE nanotubes (E=S, Se, Te; see picture) have been synthesized by a novel biomolecule‐assisted method at room temperature. The precursor nanowires self‐assembled from nanocrystals synthesized in the presence of cysteine play crucial roles as both the lead source and template in the formation of the nanotubes, which exhibit an obvious quantum confinement effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 44 publications
3
85
0
2
Order By: Relevance
“…It is also noteworthy that EN has played a crucial role for in the formation our 1D-nanorod structure. In fact, similar role of EN has also been found for the formation of many anisotropic structures on various materials, such as nanowire, nanorod, and nanosheet/plate and so on [41][42][43][44][45] . It was proposed that atoms on coherent {111} twin plane possessed high coordination number and had relatively low formation energy even comparable to the normal {111} facets 27,[46][47][48] .…”
Section: Resultsmentioning
confidence: 94%
“…It is also noteworthy that EN has played a crucial role for in the formation our 1D-nanorod structure. In fact, similar role of EN has also been found for the formation of many anisotropic structures on various materials, such as nanowire, nanorod, and nanosheet/plate and so on [41][42][43][44][45] . It was proposed that atoms on coherent {111} twin plane possessed high coordination number and had relatively low formation energy even comparable to the normal {111} facets 27,[46][47][48] .…”
Section: Resultsmentioning
confidence: 94%
“…S-12 and S-13 in the ESM) showed that PbTe nanoparticle networks were also obtained. As indicated by the formation of HSCH 2 CH(NH 2 )COO-Pb-OH in the reaction of Pb 2+ and cysteine under weakly basic conditions, Pb 2+ ions have a stronger interaction with -COO than with -SH groups [35], in contrast to the case for Cd 2+ . We believe that solvation of Pb 2+ in aqueous media attenuates the binding capability of -COO with Pb 2+ , and consequently leads to the formation of networks.…”
Section: Resultsmentioning
confidence: 97%
“…[29][30][31][32][33][34][35][36] Murray et al first synthesized monodispersed PbSe quantum dots, [37] but a number of other strategies have now been developed. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Interestingly, all these methods involve the use of separate metal and chalcogenide sources. We have reported the use of [bis(diselenoimidodialkylphosphinato)lead(II)] [Pb{N(PR 2 Se) 2 2 ] complexes as singlesource precursors for the deposition of PbSe thin films by low-pressure LP-CVD and aerosol-assisted (AACVD) experiments.…”
Section: Introductionmentioning
confidence: 99%